Digital Transformation: Challenges And Implementation Electronic Medical Record System In Indonesia - Ni Luh Arum Puspitaning Ati (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2024)
Medical records play a pivotal role in ensuring the delivery of quality healthcare services. However, the fragmented nature of medical record data across different health services leads to redundancy in health administration and implementation challenges. This research aims to delineate the implementation of an electronic medical record (EMR) system in health service agencies and the associated challenges in Indonesia. Employing a literature review method utilizing the Google Scholar database, the study conducted article searches using Indonesian keywords such as "implementation," "application," "medical records," and "electronics." Article selection followed the PRISMA method, identifying 8 articles meeting the criteria. The findings reveal that EMR implementation in Indonesia has been adopted by various institutions and health service facilities, yielding positive impacts. Nevertheless, several obstacles persist, including the scarcity of qualified resources, the need to enhance digital literacy and training among human resources, and comprehension of electronic medical record workflows. Addressing these challenges requires concerted efforts in digital transformation to improve the quality and efficiency of healthcare services in Indonesia.